Influence of Waste Marble Powder and Waste Granite Powder on the Mechanical and Durability Performance of Concrete - Engr Shafi Ullah; Muhammad Rehan Shahid; Shadab Tariq; Ammad Ahmad Khan (NAROTAMA UNIVERSITY, Indonesia, 2021)
Industries produces large amount of marble and granite waste powder. These wastes are of two types, one of them is wet form which is impure form because it mixes with soil. And the other one is in powder form which is the pure form of marble waste and granite waste. These wastes are dumped in to the open land which cause serious environmental issues such as land problem, water problem and other deterioration. We can use these wastes to overcome environmental issues. Moreover, we can use these wastes in concrete to reduce construction economy. Waste marble powder, when we use in concrete, gives us good result in mechanical and durability characteristic of concrete. We used marble powder and granite powder with limited replacement of cement at 0%, 5%, 10% to check the performance of concrete in its mechanical and durability characteristics. This thesis describes a detailed experimental study on concrete’s tensile strength and compressive strength and concrete water absorption. Better outcomes were obtained at 5-10% replacement of cement with these wastes. Concrete’s durability and mechanical characteristics were improved by increasing waste granite with limited replacing of cement up to 10%. Determined Results show that a little content of marble dust and waste granite powder with limited replacement of cement will lower construction economy, reduce the cement quantity and gives better results in compressive strength